The Meaning of Tepak Sirih Tradition In Tanjungbalai Malay Wedding Ceremony - Ade Irma Marpaung; Zainuddin Zainuddin; Busmin Gurning (State University of Medan, 2019)
This study is concerned at finding the meanings of Tepak Sirih tradition in Tanjungbalai Malay wedding ceremony. either it is the meaning of offering tepak sirih and the meanings that found in all objects that needed to practice tepak sirih tradition. This study also concerned on how and why the meanings realized in practicing tepak sirih. The research method used in this paper is descriptive qualitative method which is related to the grounded theory where the meanings are elaborated by using Roland Barthes’s Semiology Theory. The interview was assisted by two interviewees who are expert about Tanjungbalai Malay culture and tradition and they are the speakers in every ceremony of Malay in Tanjungbalai. The results showed that offering tepak sirih have different meaning in different event. Merisik, meminang and Hempang pintu are three events that use tepak sirih tradition in Tanjungbalai Malay wedding but only hempang pintu which uses tepak sirih in the wedding ceremony. The writer found There were 11 dennotative meanings, 7 connotative meanings and two myths in all objects that needed in doing tepak Sirih tradition. The reason Tepak sirih is seen as the tool of communication or the opening speech in Tanjungbalai Malay wedding ceremony lies on the history of Tanjung balai Malay living in the past.Keywords: Semiotic or Semiology, Tepak sirih, Tanjungbalai Malay